2016
DOI: 10.1172/jci.insight.88628
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte activation gene 3 and coronary artery disease

Abstract: BACKGROUND:The lipoprotein scavenger receptor BI (SCARB1) rs10846744 noncoding variant is significantly associated with atherosclerotic disease independently of traditional cardiovascular risk factors. We identified a potentially novel connection between rs10846744, the immune checkpoint inhibitor lymphocyte activation gene 3 (LAG3), and atherosclerosis. METHODS:In vitro approaches included flow cytometry, lipid raft isolation, phosphosignaling, cytokine measurements, and overexpressing and silencing LAG3 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…Risk factors for CVD are under intense investigation and involve both traditional and non-traditional factors. A study by Golden et al [ 52 ] found that the lipoprotein scavenger receptor class B type 1 (SCARBI) rs10846744 noncoding variant is significantly associated with atherosclerotic disease independently of traditional cardiovascular risk factors. They identified a connection between rs10846744 with sLAG-3 in plasma and concluded that plasma sLAG-3 is an independent predictor of HDL-cholesterol levels and CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for CVD are under intense investigation and involve both traditional and non-traditional factors. A study by Golden et al [ 52 ] found that the lipoprotein scavenger receptor class B type 1 (SCARBI) rs10846744 noncoding variant is significantly associated with atherosclerotic disease independently of traditional cardiovascular risk factors. They identified a connection between rs10846744 with sLAG-3 in plasma and concluded that plasma sLAG-3 is an independent predictor of HDL-cholesterol levels and CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in 2016, a large population based study revealed that subjects heterozygous for the P376L mutant form of SR-BI showed significantly increased levels of plasma HDL-cholesterol and had increased risk of cardiovascular disease [11**], now demonstrating that SR-BI in humans was a significant determinant of cardiovascular disease. In further support, the rs10846744 SNP which resides within the enhancer region of SCARBI was recently shown to be significantly associated with atherosclerotic disease [12]. In light of these new findings, some 23 years since SR-BI’s discovery, it appears now that SR-BI has been “re-discovered” as relevant to human disease in a variety of new pathways and mechanisms, as will be covered in this review.…”
Section: Introductionmentioning
confidence: 88%
“…SR-BI’s role in inflammation has been well studied and now also shown to be relevant in humans [12,13]. Using RNA-sequencing data, lymphocyte activating 3 (LAG3) RNA was identified as a major target driving the effect of SR-BI on inflammation, since its expression was significantly lower in homozygous carriers of the SR-BI rs10846744 risk allele [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells presenting the noncoding variant produced less amounts of LAG-3 under basal conditions and following BCR engagement. Plasma LAG-3 levels were found lower in hyperalphalipoproteinemia patients and significantly associate with HDL and IL-10 concentration in plasma (74). Therefore, LAG-3 may confer protective immune response in the heart, although this hypothesis was not formally addressed.…”
Section: Tigit Tim-3 and Lag-3mentioning
confidence: 97%